Strategi Kebijakan Pendidikan Berkualitas pada Madrasah Aliyah Negeri di Papua - Dwiharjanto (JURNAL ILMIAH GEMA PERENCANA, 2025)
This Policy Paper is written to analyze the education policy strategy of State Islamic Senior High Schools (MAN) in Papua to realize quality education amidst various limitations. The approach used is qualitative with data collection techniques including the study of education policy documents, in-depth interviews with stakeholders such as madrasah principals, persons in charge of data, and conducting participatory observations in several State Islamic Senior High Schools (MAN) spread across the Papua region. The collected data are analyzed descriptively-interpretively, with a focus on identifying policy patterns, implementation challenges, and the resulting impacts. A more detailed analysis is conducted to understand the socio-cultural and geographical context of Papua that influences the effectiveness of the policy. This Policy Paper also evaluates the suitability between the formulated policies and real needs in the field and identifies potential innovations that can be applied to overcome obstacles. The findings of this Policy Paper are expected to provide constructive recommendations for the development of education policies of State Islamic Senior High Schools (MAN) in Papua, with the ultimate goal of increasing access and quality of education for the younger generation in the region. Based on the analysis and discussion, the author proposes a policy of optimizing the budget and infrastructure governance to answer the problem statement. The Head of the Papua Province Ministry of Religion Regional Office is expected to initiate a progressive budget proposal to fulfill supporting facilities for educational units.